Revealing immune infiltrate characteristics and potential immune-related genes in hepatic fibrosis: based on bioinformatics, transcriptomics and q-PCR experiments - Bai, Yan-Ming; Liang, Shuang; Zhou, Bo (Frontiers in Immunology, 2023)
Background: The occurrence and progression of hepatic fibrosis (HF) is accompanied by inflammatory damage. This research focused on the identification of immune genes and biological pathway which involved in fibrosis formation and inflammatory damage in HF. Methods: The crucial module genes for HF were screened according to weighted gene co-expression network analysis (WGCNA). The crucial module genes were mapped to immune-related genes obtained from the ImmPort database to obtain the hepatic fibrosis immune genes (HFIGs). In addition, the functional enrichment analyses were performed on HFIGs. Then, the protein-protein interaction (PPI) network was conducted on HFIGs and hub genes were identified from the PPI network. Moreover, immune infiltration analysis was performed to identified correlation between hub gene and immune cell infiltration. To verify the reliability of bioinformatics analysis, a rat model of CCl4-induced HF was established, followed by transcriptome sequencing and quantitative reverse transcription (q-PCR) experiments were performed in HF rats and normal rat liver tissues. Results: 98 HFIGs were screened and these genes were mainly involved in inflammation-related biological pathways such as NOD-like receptor signaling pathway, NF-kappa B signaling pathway and PI3K-Akt signaling pathway. From the PPI network, 10 hub genes were identified, including CXCL8, IL18, CXCL10, CD8A, IL7, PTPRC, CCL5, IL7R, CXCL9 and CCL2. Immune infiltration analysis showed that Macrophages M1, T cells gamma delta, B cells naive, Macrophages M2, B cells memory, T cells regulatory (Tregs) and NK cells were significantly correlated with the HF process and hub gene expression was significantly correlated with these immune cells. Notably, most of the biological pathways HFIGs riched and all the hub gene expression except CXCL8 were validated in subsequent transcriptome and qRCR experiments. Conclusions: The immune genes CXCL8, IL18, CXCL10, CD8A, IL7, PTPRC, CCL5, IL7R, CXCL9 and CCL2 may play an essential role in the fibrosis formation and inflammatory damage in HF. The outcomes of this research provide a basis for the study of the immune mechanisms of HF and contribute to the diagnosis and prevention of HF in clinical practice.